RANCANG BANGUN GRATE PADA ALAT INSINERATOR - Faisal Asnan; Sigit Mujiarto; Suyitno (POLITALA PRESS, 2026)
Waste is a major issue in Indonesia, with production exceeding 67 million tons annually. One effective method for waste treatment is combustion using an incinerator. This study aims to design and build a grate as an additional component to improve the efficiency of the combustion process in an incinerator. The designed grate consists of three main parts: a manual actuator, a drying staircase, and a combustion chamber. The design was created using AutoCAD and SketchUp software, and experiments were conducted using three types of waste: dry, wet, and mixed. The test results show that the addition of the grate accelerates the combustion process and enhances user safety. The highest combustion rate was achieved with dry waste at 2.95 grams/second, followed by wet waste (2.50 grams/second), and mixed waste (2.10 grams/second). The grate also helps reduce moisture content before the waste enters the combustion chamber, contributing to smoke reduction and improved combustion efficiency. This design is expected to offer a practical and efficient solution for small to medium-scale waste management.